Strong light–matter coupling in microcavities characterised by Rabi-splittings comparable to the Bragg stop-band widths. (9th November 2021) - Cao, Junhui; De Liberato, Simone; Kavokin, Alexey V
Abstract: The vacuum Rabi splitting of polaritonic eigenmodes in semiconductor microcavities scales with the square root of the oscillator strength, as predicted by the coupled oscillator model and confirmed in many experiments. We show here that the square root law is no more applicable if the Rabi splitting becomes comparable or larger than the stop-band width of the Bragg mirrors forming the cavity. Once the oscillator strength becomes large enough, the material hosting excitons hybridises with the quasi-continuum microcavity Bragg modes lying outside of the stop-band, thus forming a novel kind of polaritonic resonance. We study this physics considering both two- and three-dimensional excitonic materials embedded in the microcavity. We highlight the varied phenomenology of those polaritons and develop a theoretical understanding of their most peculiar features.